2000
DOI: 10.1007/s003470070025
|View full text |Cite
|
Sign up to set email alerts
|

Lokales Cyclosporin A bei Nummuli nach Keratoconjunctivitis epidemica

Abstract: CSA was effective in eliminating or reducing nummuli in the majority of patients. More than one-half of the responding eyes had a complete cure and did not experience recurrences after stopping therapy. We therefore consider topical CSA to be a safe and effective alternative to topical steroids for treating nummular infiltrates after AK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 0 publications
0
24
1
2
Order By: Relevance
“…29 Cyclosporine was specifically explored for treating symptoms caused by subepithelial infiltrates. 12,13,19,20 One percent CsA administered 4 times a day for 21 days during acute infection produced earlier subjective improvement of local symptoms and a trend toward a lower incidence of corneal opacities. 20 In a second study, the majority of patients with longstanding established CSE were successfully treated with 2% CsA with reduction or elimination of SEIs and successful weaning off therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 Cyclosporine was specifically explored for treating symptoms caused by subepithelial infiltrates. 12,13,19,20 One percent CsA administered 4 times a day for 21 days during acute infection produced earlier subjective improvement of local symptoms and a trend toward a lower incidence of corneal opacities. 20 In a second study, the majority of patients with longstanding established CSE were successfully treated with 2% CsA with reduction or elimination of SEIs and successful weaning off therapy.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a second study, the majority of patients with longstanding established CSE were successfully treated with 2% CsA with reduction or elimination of SEIs and successful weaning off therapy. 19 Similarly, Levinger et al 13 reported improvement in vision and satisfaction with topical 1% CSA in 9 patients with subepithelial corneal infiltrates secondary to adenoviral keratoconjunctivitis. Romanowski et al found that treatment with both 2.0 and 0.5% CsA in the rabbit model significantly reduced the formation of SEIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These nummular opacities or infiltrates can impair visual function and can persist for months to years. 4 Histopathological investigation of focal biopsy samples revealed subepithelial infiltrates of lymphocytes, histiocytes, and fibroblasts accompanied by a disruption of the collagen fibers of the Bowman layer. 5,6 The pathogenesis of the nummular opacities most likely includes a persisting viral replication in subepithelial keratocytes, triggering an immunological host reaction.…”
mentioning
confidence: 99%